Psikologi Sastra dalam Naskah Drama Kekasihku Ingin Meraih Hujan dari Jendela Kamar dan Love Karya Ari Pahala Hutabarat dalam Kumpulan Naskah Drama Orang-Orang Setia Teater Satu - Surya, Surya Febrirezki (J-LELC: Journal of Language Education, Linguistics, and Culture, 2022)
This research is motivated by several things, namely: (1) Seeing the many aspects of literary psychology in the collection of drama scripts from Ari Pahala Hutabarat's Theater One, (2) So far, research on drama scripts has not been done much. In fact, in UIR, especially FKIP, research on scripts using literary psychology theory is still rarely carried out and this is due to the tendency for people to understand and recognize a drama, always staging it compared to the drama script itself. The problem in this research is "What is the personality structure of the characters related to the id, ego, and superego in a collection of theatrical drama scripts by Ari Pahala Hutabarat?". The theory used to analyze this research is Sigmund Freud's theory. The approach used is a qualitative approach, this type of research is library research. The method used is descriptive method, the data analysis technique used is content analysis technique. The results showed that there were id, ego, and superego in a collection of drama scripts from Ari Pahala Hutabarat's Satu Karya Theater. The results of the most dominant literary psychology research is the ego personality structure while the id and superego personality structures have a balance in the character. Although there is a balance in the personality structure of the characters in the script, it does not guarantee that there will be no conflict. The conflicts that occur are in a state of war inside him, restless, restless, depressed and others. The psychology in the drama script Teater Satu shows that whatever we do in real life happens based on what we think so that when we think positively without realizing it helps humans to balance what we think with real life.